Faecal prevalence of extended-spectrum ß-lactamase (ESBL)-producing coliforms in a geriatric population and among haematology patients - Nurul Atifah, M.A.; Loo, H.K.C.; Wong, E.H.; Subramaniam, G.; Ho, S.E.; Selvi, P.; Parasakthi, N.; Kamarulzaman, A. (Malaysian Society of Pathologists, 2005)
Antimicrobial resistance to the extended-spectrum cephalosporins is increasingly reported worldwide. In the local setting, nosocomial infections with multi-resistant Gram-negative bacilli are not uncommon and are a growing concern. However, there is limited data on the carriage rates of such organisms in the local setting. In May 2001, a prospective study was carried out to determine the enteric carriage rates of ceftazidime-resistant Gram negative bacilli (CAZ-R GNB) among residents of nursing homes and from in-patients of the geriatric and adult haematology wards of University Malaya Medical Centre. Ceftazidime-resistant Gram-negative bacilli (CAZ-R GNB) were detected in 25 samples (30%), out of which 6 were from nursing home residents, 5 from geriatric in-patients and 14 from the haematology unit. A total of 28 CAZ-R GNB were isolated and Escherichia coli (10) and Klebsiella pneumoniae (7) were the predominant organisms. Resistance to ceftazidime in E. coli and Klebsiella was mediated by extended-spectrum beta-lactamases (ESBLs). Although the majority of the CAZ-R GNB were from patients in the haematology ward, the six nursing home residents with CAZ-R GNB were enteric carriers of ESBL-producing coliforms. Prior exposure to antibiotics was associated with carriage of ESBL organisms and to a lesser extent, the presence of urinary catheters.